Supply chain proposal to reduce cold storage costs of a super market meat cold room, Lima- 2024 - Valdiviezo Martinez, Astrid Araceli; ESCOBAR POMA, LUCERO MARIEL; Miñan Olivos, Guillermo Segundo (LACCEI, 2024)
The objective of the study was to propose an optimized supply chain to reduce storage costs in the meat cold storage room of a supermarket in Lima, Peru, in the year 2024. The methodology applied was descriptive, applied and propositional. A quantitative approach based on the collection and analysis of numerical data was used. The study included direct observation of the processes in the cold chamber, documentary analysis of previous research and the application of various analytical tools such as the Ishikawa diagram, the Pareto diagram, ABC analysis and the FIFO method. A scenario simulation was carried out to predict cost reduction. The results revealed that poor inventory turnover management and inadequate implementation of the FIFO method are the main causes of high warehousing costs. A cumulative negative difference of $19,528.11 was identified between actual and budgeted costs during the first four months of 2024. The implementation of inventory management software, along with staff training and warehouse reorganization, is projected to be an effective solution to reduce these costs, with an estimated average annual savings of $5,190.9. It was concluded that the implementation of supply chain improvements, especially inventory management and staff training, is crucial to significantly reduce meat cold storage costs.